Special designed universal power switching generator for power electronics studies - Rosnazri, Ali; Ismail, Daut, Prof. Dr.; Tunku Muhammad Nizar, Tunku Mansur; Nor Hanisah, Baharudin; Irwanto, Misrun; Soib, Taib (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org